131 Can Maternal Nutrition in Dairy Cattle Impact Gut Health in Dairy Calves?. (8th October 2021) - Cangiano, Lautaro Rostoll; Malmuthuge, Nilusha; Ma, Tao; Guan, Leluo; Steele, Michael A
Abstract: The nutritional management, health and welfare of the dairy calf has historically received less attention due to limited research, and recommendations largely focused on passive transfer of immunity and early weaning strategies. Gastrointestinal diseases and disorders remain the leading cause of mortality and morbidity in dairy calves worldwide. Despite the recent thrust in dairy calf nutrition research, major knowledge gaps still exist regarding how maternal nutrition during pregnancy and postpartum impact gastrointestinal health and function, especially during the fetal and neonatal stages when the developmental plasticity is highest. Recent research has focused on how prepartum nutrition and management can influence colostrum quality and has characterized numerous bioactive proteins, lipids, and carbohydrates that may play a critical role in gastrointestinal function and development. It has also been shown that colostrum plays a fundamental role in promoting colonization with commensal bacteria; however, delaying colostrum feeding or abruptly transitioning calves from colostrum to milk decreased the colonization of beneficial bacteria and impaired gastrointestinal development. With respect to the maternal nutrient supply via milk, it is important to note that calves have been traditionally fed less than half of voluntary intake or fed milk replacer formulations that can largely differ in composition from that of maternal milk. Recent research indicated that common milk replacer formulations may impair gastrointestinal function, highlighting the need to question existing nutritional regimens. In addition, feeding prophylactic antibiotics in milk, as well as waste milk containing antibiotic residues, are common practices in the dairy industry, despite recent studies reporting that these practices can increase calf susceptibility to infections by disrupting gut microbiome and gut function. Although our knowledge how maternal factors impact the gastrointestinal tract of calves is limited, it is clear there are great opportunities to further develop prenatal and postnatal nutritional programs to improve dairy calf gastrointestinal health.